2019
DOI: 10.37673/jebi.v4i1.226
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Risiko Kegagalan Budidaya Jamur Tiram Pada Bintan Cendawan

Abstract: Tujuan dari penelitian ini adalah untuk menganalisis dan mengidentifikasi risiko kegagalan budidaya jamur tiram, dampak yang di timbulkan serta tindakan yang perlu dilakukan sebagai antisipasi dan pencegahan atas risiko-risiko pada usaha budidaya jamur tiram di Bintan Cendawan. Penelitian ini menggunakan pendekatan penelitian kualitatif deskriptif. Lokasi penelitiannya adalah di Jalan Hang Jebat Kp. Pisang RT.002/ RW.007 No.60, Kijang Kota Kecamatan Bintan Timur,Kabupaten Bintan. Teknik pengumpulan data yang d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Risk management aims to manage risk so that we can obtain the most optimal results [1]. One of the implementation of risk management in the company known is Enterprise Risk Management (ERM) [6].…”
Section: A Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk management aims to manage risk so that we can obtain the most optimal results [1]. One of the implementation of risk management in the company known is Enterprise Risk Management (ERM) [6].…”
Section: A Risk Managementmentioning
confidence: 99%
“…Related studies supporting this study include the research conducted by 1) [1] entitled "The Analysis Of Potato Chips Product Damaged Risk In Widuri Joint Venture Group", the results showed that there are several factors that can cause the failure of the production process and the product itself which was an error in the selection of raw materials, skipping the process of soaking potatoes, a mistake in the provision of lime paste, errors at controlling stove fire, and human error that have impact on the organization. 2) [6] entitled "Risk Analysis The Failure of Oyster Mushroom Cultivation On Bintan Cendawan", the results showed that there are several factors that can cause failure in the process of oyster mushroom cultivation, these factors consist of several levels so that the impact caused also has a scale or level of which can often occur until that never happens and also has a high or low impact. 3) [12], entitled "Application Of Enterprise Risk Management In Order To Improve The Effectiveness Of Operational Activities CV.…”
Section: A Risk Managementmentioning
confidence: 99%